Evaluation of Microfine Palm Oil Fuel Ash (POFA) as Cement Partial Replacement Material for Mitigation of Chloride Attack - Ahmadi, Raudhah; Syukry Saiful, Mohd; Fahmi Zawawi, Dzul; Zaman Abdul Rahman, Shahrul; Ismail, Idawati; Abdul Mannan, Mohamad; Sakura Zainal Abidin, Ana; Mohamed Nazri, Fadzli (International Journal of Engineering and Technology, 2018)
This paper investigates the effect of microfine palm oil fuel ash (POFA) as cement replacement material for mitigation of chloride attack in concrete. The raw POFA obtained from a local palm oil mill is initially grinded using Los Angeles abrasion machine, and then sieved using 150 Î¼m sieve before it is burned in a furnace at 500Â°C. The burned POFA is then grinded using electric powder grinder to obtain the targeted microfine size ranging between 1-10 Î¼m. Treated microfine POFA is used in the production of concrete samples for experimental tests; compressive strength test, sorptivity test and chloride penetration test to determine its physical properties and the chloride resistance parameter for the mitigation of chloride attack in concrete. Results showed that 20% of microfine POFA replacement in concrete gives the highest compressive strength at 56th day and reduces the rate of absorption of water and chloride penetration.Â Â